THE EFFECTIVITY OF MARRIAGE GUIDANCE IN KUA CITEUREUP TO MAINTAIN HOUSEHOLD INTEGRATION (EFEKTIVITAS BIMBINGAN PERKAWINAN DI KUA CITEUREUP DALAM MENJAGA KEUTUHAN RUMAH TANGGA) - Mukhtar Mukhtar; Yusuf Firdaus (al-Afkar, Journal For Islamic Studies, 2019)
This study discusses the effectiveness of marital guidance in KUA Citeureup in maintanining the integrity household countained from the cause due to the high divorce in Indonesia, especially for muslim in Indonesia, where the government has issued a policy that the bride and groom thas prospective brides who want to marry are required to follow the guidance of marriage in advance. despite the policy being issued, the fact remains that many bride and groom who do not follow the marriage guidance even tends to underestimate the importance of following marital guidance. this research uses mix method approach method and using field research method. the main source of this research is the religious affairs office and the bride and groom who married in the office of religious affairs. so the authors get data on the extent to which effectiveness of marital guidance that has been provided by officials of the citeureup religious affairs office in maintaining the integrity of the household. in the discussion of the effectiviness of marital guidance in maintaining the integrity of this household has two important points that need to be studied, how far the effectiviness of marital guidance that has been given by the officers kua citeureup to the bride and groom in maintaining the integrity of the household and any factors that make many bride and groom are still unable to attend marriage counselling that has been held by the office of religious affairs. Penelitian ini membahas tentang efektivitas bimbingan perkawinan di KUA dalam menjaga keutuhan rumah tangga yan disebabkan akibat tingginya tingkat perceraian yang terjadi di Indonesia, khususnya bagi umat muslim di Indonesia, dimana pemerintah telah mengeluarkan kebijakan bahwa para catin yang ingin melangsungkan pernikahan diharuskan untuk mengikuti binwin terlebih dahulu. Meskipun telah dikeluarkan kebijakan tersebut, faktanya masih banyak para catin yang tidak mengikuti binwin bahkan cenderung menyepelekan mengenai urgensinya mengikuti binwin sebelum menikah. Penelitian ini menggunakan metode Mixed method, yakni metode penelitian gabungan antara kualitatif dan kuantitatif. Sumber utama penelitian ini adalah para catin yang menikah di KUA Citeureup, sehingga penulis mendapatkan data sejauhmana efektivitas binwin yang sudah diberikan kepada para catin dalam menjaga keutuhan rumah tangga. Dalam pembahasan tentang efektivitas bimbingan perkawinan dalam menjaga keutuhan rumah tangga ini memiliki dua poin penting yang perlu dikaji, yakni sejauhmana efektivitas binwin yang telah diberikan kepada para catin dalam menjaga keutuhan rumah tangga dan faktor apa sajakah yang membuat para catin masih banyak yang belum dapat menghadiri bimbingan perkawinan yang telah diadakan oleh KUA Citeureup.